Sound within Sound : A History of Radical Twentieth Century Composers. - Molleson, Kate (London : Faber, 2022)
Carillo, Juliàn ; Crawford, Ruth ; Smetak, Walter ; Maceda, José ; Ustvolskaya, Galina ; Guèbru, Emahoy Tsegué-Mariam ; Pade, Else Marie ; Abrams, Muhal Richard ; Radigue, Eliane ; Lockwood, Annea
boek